Factors associated with longer time to treatment in the care of patients transported by emergency medical services for suspected acute coronary syndromes and ST-segment elevation myocardial infarction. - Sullivan, Alison. (2017)
Abstract: Rapid treatment of acute coronary syndromes (ACS) is important, but the causes of delay in emergency medical services (EMS) care of ACS are not well understood. We conducted a cohort study of data from a multicenter randomized controlled trial of EMS treatment of people calling 9-1-1 for symptoms suggesting ACS using hierarchical multiple regression of elapsed time and the presence or absence of delay. A total of 54,230 individuals aged 18 or older called 9-1-1 and had an out-of-hospital electrocardiogram (ECG) performed; 871 were included in the trial for presumed ACS, 303 of whom had STEMI and percutaneous coronary intervention. Median times from EMS arrival to ECG were 15 minutes among all participants, 11 minutes in those with presumed ACS, and 10 minutes for those with STEMI. Median on-scene times were 20 minutes for those with presumed ACS, and 16 minutes for those with STEMI. Women had longer time from EMS arrival to ECG (7% among all participants, 12% among those with presumed ACS, and 20% among those with STEMI) and on-scene times (9% with presumed ACS, and 12% with STEMI). Older individuals had longer times (among those with presumed ACS; EMS to ECG 8%, on-scene time 10%). Members of minorities and those without chest pain had longer time from EMS arrival to ECG (among participants with presumed ACS, 13% and 16% compared to their respective counterparts). Women and older individuals also had longer hospital and total times (hospital arrival to balloon 10% and 13%, medical contact to balloon inflation 9% and 18%, symptom onset to balloon inflation 18% and 13%, respectively). Weekend and night presentations were only associated with longer hospital times (hospital arrival to balloon inflation 31% and 24%, medical contact to balloon inflation 19% and 32%, respectively; all p values < 0.05). Hospital arrival to balloon inflation was double the time in EMS care (62 vs. 30 minutes) for participants with STEMI. We found delays throughout the entire spectrum of care, which resulted in larger magnitude differences in total times for women and older individuals. A comprehensive approach to reduce delays is needed.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Clinical & Translational Science.; Advisors: Harry Selker, and Joni Beshansky.; Committee: Robin Ruthazer.; Keyword: Medicine.